Steering Surface Reaction Dynamics with a Self‐Assembly Strategy: Ullmann Coupling on Metal Surfaces. Issue 42 (6th September 2017) - Zhou, Xiong; Wang, Chenguang; Zhang, Yajie; Cheng, Fang; He, Yang; Shen, Qian; Shang, Jian; Shao, Xiang; Ji, Wei; Chen, Wei; Xu, Guoqin; Wu, Kai
Abstract: Ullmann coupling of 4‐bromobiphenyl thermally catalyzed on Ag(111), Cu(111), and Cu(100) surfaces was scrutinized by scanning tunneling microscopy as well as theoretical calculations. Detailed experimental evidence showed that initial formation of organometallic intermediates on the surface, as self‐assembled structures or sparsely dispersed species, is determined by the subsequent reaction pathway. Specifically, the assembled organometallic intermediates at full coverage underwent a single‐barrier process to directly convert into the final coupling products, while the sparsely dispersed intermediates at low coverage went through a double‐barrier process via newly identified clover‐shaped intermediates prior to formation of the final coupling products. These findings demonstrate that a self‐assembly strategy can efficiently steer surface reaction pathways and dynamics. Abstract : Self‐assembly‐steered surface reaction dynamics : The Ullmann coupling of 4‐bromobiphenyl on silver and copper surfaces occurs by two pathways: 1) unassembled intermediates form clover‐shaped structures prior to formation of the final product, or 2) self‐assembled organometallic intermediates form the final product directly.